Analysis of catching of sea cucumber (Stichopus variegatus) in Kramian islands, Sumenep regency, East Java - Dony Prasetyo; Riza Rahman Hakim; Andriyanto Andriyanto (IJOTA (Indonesian Journal of Tropical Aquatic), 2021)
Kramian Island is located in the north of the Masalembu Islands, East Java. This area has good sea cucumber resources, but the rules on the prohibition of overfishing of sea cucumbers have not been implemented by the government in the Kramian Islands, so that fishing activities carried out by fishermen, continuously regardless of the type and size of sea cucumbers, can cause sea cucumbers in the wild to run out and the impact of sea cucumbers will be extinct. The research was conducted with the aim of knowing the fishing location, fishing method, sea cucumber species, number of catches, and benefits of sea cucumber catch. This research was conducted in March-June 2020. The method used in the study was observed with fishermen. The results of the discovery of the location of sea cucumbers using GPS, there were 3 types of sea cucumbers, namely Tanduk (Stichopus variegatus), Kapuk (Stichopus variegatus), and Susu (Holothuria rigida). Sea cucumber catch in March (253.4 kg), April (261.1 kg), May (124.1 kg), June (733.6 kg). The highest sea cucumber catch data occurred in June, while the lowest catch occurred in May.